(untitled) (Journal of the College of Basic Education, 2022)
The research was concerned with studying the importance of the Arabic letter as a civilizational symbolism that includes the emotional and faith dimensions in Islamic art, including the Arabic calligraphy arts, in addition to its effectiveness and the achievement of communication reinforcement in contemporary plastic paintings.The study consisted of four chapters, the first chapter of which concerned the methodological framework for it.Discovering the role of the Arabic letter in enhancing communication in contemporary Iraqi painting